Still different after all these years: Solidarity in East and West Germany - Jeannette Brosig; Christoph Helbach; Axel Ockenfels; Joachim Weimann (Verein für Socialpolitik, 2010)
Motivated by recent research on survey data, we test the influence of the political regime on social norms under controlled laboratory conditions. Comparing solidarity behavior revealed by East and West Germans in 1995 and 2009, we find that East Germans persistently show much less solidarity than West Germans. Twenty years after the fall of the Berlin Wall, social norms of solidarity have not converged. This suggests that norms of social behavior change much more slowly than the political environment.
Keywords: C91; D63; P51; 330; Experimental Economics; Solidarity; Norms; Cross-culture study